2004
DOI: 10.1164/rccm.200312-1686oc
|View full text |Cite
|
Sign up to set email alerts
|

Gene Microarray Analysis of Peripheral Blood Cells in Pulmonary Arterial Hypertension

Abstract: The importance of genetic predisposition, inflammation, and autoimmune mechanisms in the development of pulmonary arterial hypertension (PAH) is becoming increasingly clear. We hypothesized that the analysis of gene expression profiles from peripheral blood mononuclear cells would distinguish patients with PAH from normal volunteers. We also hypothesized that a subset of genes would discriminate between patients with idiopathic PAH and pulmonary hypertension related to secondary causes. Mononuclear cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 50 publications
8
112
0
4
Order By: Relevance
“…We forecast that the pathogenetic insights will allow one to further reclassify the disease as angioproliferative [120] or myofibroblastic (as in idiopathic pulmonary fibrosis), neoplastic-like, or a reaction to injury, with clear implications to biomarker discovery, disease-tailored therapies, genetic association studies, etc. Based solely on the advances in the past 10 years, there is the potential to refine the diagnostic tools using genomics of peripheral blood cells of PH patients [121] and also to breakdown the apparently unifying pathology of severe PH using genomics applied to lung tissue [122]. As illustrated in the color Figures, a lung with severe PH shows a range of ongoing vascular lesions, with distinct severities and cellular compositions.…”
Section: Discussionmentioning
confidence: 99%
“…We forecast that the pathogenetic insights will allow one to further reclassify the disease as angioproliferative [120] or myofibroblastic (as in idiopathic pulmonary fibrosis), neoplastic-like, or a reaction to injury, with clear implications to biomarker discovery, disease-tailored therapies, genetic association studies, etc. Based solely on the advances in the past 10 years, there is the potential to refine the diagnostic tools using genomics of peripheral blood cells of PH patients [121] and also to breakdown the apparently unifying pathology of severe PH using genomics applied to lung tissue [122]. As illustrated in the color Figures, a lung with severe PH shows a range of ongoing vascular lesions, with distinct severities and cellular compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Bull et al demonstrated that gene expression profiling of PBMCs efficiently discriminates between patients with PAH and normal volunteers and identifies PAH-specific genes (11,12). We therefore hypothesized that gene expression profiling of PBMCs from SSc patients with PAH can identify PAH-specific genes despite the presence of dysregulated immunity in these patients.…”
Section: Introductionmentioning
confidence: 93%
“…Bull et al looked at the gene expression profiling of PBMCs to look for genetic signatures of pulmonary arterial hypertension (PAH). The gene expression profile of 16 patients with PAH showed 106 differentially expressed genes that distinguished between controls and PAH patients with 95-100% accuracy (P \ 0.002) (Bull et al 2004. However, within the PAH patients, unsupervised cluster analysis failed to show a genetic signature that reliably distinguished between secondary pulmonary arterial hypertension and idiopathic pulmonary arterial hypertension.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%